2003
DOI: 10.1256/qj.02.151
|View full text |Cite
|
Sign up to set email alerts
|

A mechanism of the Madden–Julian Oscillation based on interactions in the frequency domain

Abstract: SUMMARYThe surface and boundary-layer uxes of moisture exhibit a large ampli cation as the waves in the Madden-Julian Oscillation (MJO) time-scales interact with synoptic time-scales of 2 to 7 days. This ampli cation is clearly seen when the datasets are cast in the frequency domain for computations of the respective uxes. Those ux relations carry triple-product nonlinearities, and the uxes on the time-scale of the MJO are evaluated using co-spectra of triadal frequency interactions. The trigonometric selectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(21 citation statements)
references
References 41 publications
1
20
0
Order By: Relevance
“…It has been identified from various fields such as zonal and divergent wind, SLP, and OLR in the tropics (Madden and Julian, 1972;Kiladis and Weickmann, 1992), and here we choose to use OLR. For details on the mechanisms involved in MJO the reader is referred, for example, to Hendon and Salby (1994), Matthews (2000), and Krishnamurthi et al (2003). The OLR data used here come from NCEP/NCAR reanalyses over the tropical region from 30°S to 30°N.…”
Section: Application To Outgoing Long Wave Radiationmentioning
confidence: 99%
“…It has been identified from various fields such as zonal and divergent wind, SLP, and OLR in the tropics (Madden and Julian, 1972;Kiladis and Weickmann, 1992), and here we choose to use OLR. For details on the mechanisms involved in MJO the reader is referred, for example, to Hendon and Salby (1994), Matthews (2000), and Krishnamurthi et al (2003). The OLR data used here come from NCEP/NCAR reanalyses over the tropical region from 30°S to 30°N.…”
Section: Application To Outgoing Long Wave Radiationmentioning
confidence: 99%
“…Thus the effect of one scale to other scale may also be known. The device was extensively used by Krishnamurti et al (2003); Krishnamurti and Chakraborty (2006) to delineate the nonlinear aspects of the intraseasonal oscillation. The formalism of the triad interaction entails the Fourier series of nonlinearities associated with the triple product term.…”
Section: S Dementioning
confidence: 99%
“…The previous studies have shown the close relation between the synoptic-scale disturbances and the MJO, and suggested that the synoptic-scale disturbances could be one important factor to trigger the MJO. Krishnamurti et al (2003) have shown that the interaction of MJO time-scales with synoptic time-scales in the constant flux and boundary layers leads to a large amplification at the MJO time-scales. Matthews and Kiladis (1999) found that the high-frequency waves propagating into the Indian Ocean region at the beginning of the MJO cycle, which may be important in the initiation of intraseasonal convective anomalies there.…”
Section: Introductionmentioning
confidence: 99%